TRANSACTIONAL LEADERSHIP STYLES ON EMPLOYEE PERFORMANCE - Enjang Kusnadi (SEAN Institute, 2022)
This study tries to evaluate whether or not transformational and transactional leadership styles have a partial or simultaneous effect on employee performance. In this study, the population consisted of 175 employees, and a sample was drawn using the Slovin formula. The method of research employed is descriptive verification with a quantitative approach, and the primary and secondary data sources employed are primary and secondary data, respectively. Descriptive statistics, validity tests, reliability tests, correlation tests, and hypothesis testing including the multiple linear regression test, the t test, the f test, and the coefficient of determination test are employed (R 2). This investigation was conducted on AL Islah Education Foundation employees in Jakarta. The employee performance is influenced by the outcomes of the partial test for transformational leadership style variables. Then, the partial test (t test) results for the transactional leadership style variable have an effect on employee performance. In addition, the findings of the simultaneous test (F test) indicate that both transformational and transactional leadership styles have a favorable and statistically significant impact on employee performance. Knowing that the coefficient of determination (r 2) is 0.63, the contribution of transformational leadership style and transactional leadership style to employee performance is 63%, while the remaining 37% is influenced by variables outside the scope of this study